Can Cultural Capital and the Right to the City Explain Class-Based Alienation in Thailand’s Art Museums? - Naknawaphan, Amika; Naknawaphan, Onnutcha (Journal of Contemporary Urban Affairs, 2025)
Contemporary art museums in Thailand often fail to engage working-class communities, revealing a disconnect between institutional narratives and the lived realities of marginalized urban citizens. This study investigates how cultural exclusion reflects broader socio-economic inequality, contributing to the journal’s focus on the economic ramifications of urbanization. Through qualitative fieldwork and interviews at four institutions—BACC and MOCA (Thailand), Tate Modern (UK), and Pirelli HangarBicocca (Italy)—it identifies four key dimensions of alienation: psychological, spatial, socio-cultural, and economic. Drawing on Bourdieu’s concept of cultural capital and Lefebvre’s Right to the City, the research introduces a typology of alienation that functions as both a theoretical contribution and a practical tool. It demonstrates that exclusion stems not only from cost but also from curatorial tone, spatial design, and symbolic inaccessibility. By centering the perspectives of lower-income participants, this study contributes an interdisciplinary framework that bridges museology, urban studies, and critical ethnography. By situating cultural alienation within the socio-economic transformations of contemporary urbanization, the study demonstrates how exclusion from museums parallels broader patterns of economic inequality and urban segregation in Thailand. Ultimately, it argues that inclusive cultural infrastructure is essential for fostering urban resilience and democratic participation.